Single‐Site Molecular Ruthenium(II) Water‐Oxidation Catalysts Grafted into a Polymer‐Modified Surface for Improved Stability and Efficiency - Dr. Yosra M. Badiei; Oshane Annon; Christina Maldonado; Emily Delgado; Caroline Nguyen; Christina Rivera; Dr. Clive Li; Abril Flores Ortega (ChemElectroChem, 2023)
Abstract Water‐oxidation is a mechanistic bottleneck in artificial photosynthesis that is critical for achieving sustainable energy‐to‐fuel conversion. Grafting molecular water‐oxidation catalyst assemblies on the surface of a polymer can engender better stability and higher efficiency. Herein, we present a hybrid construct which consists of a molecular single‐site RuCat1 encapsulated into a UV cross‐linked polymer assembly on an F‐doped tin oxide (FTO). Incorporation of high‐density surface‐binding sites (COO− groups) resulted in a high surface loading of the RuCat1 and surface stability as shown from ATR‐FTIR, UV‐vis and cyclic voltammetry data. Furthermore, we found that the grafted RuCat1 into the polymer brush layers promotes pH‐dependent electrocatalytic water‐oxidation with a turnover frequency of 0.45 s−1 and an estimated 88 % faradaic efficiency during control potential electrolysis at pH 8.5. The general applicability of this approach is illustrated by screening a series of molecular single‐site catalysts which points to the importance of electrostatic interactions as well as hydrogen bonding in the functionalization of the electrode.